Effect of Soil Saturation On Seismic Performance of A Structure: A Numerical Approach - Nadir Karahan; Fatih Göktepe; Erkan Çelebi (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The aim of this study is to investigatethe impact of soil saturation on the seismic performance of a structure whensubjected to earthquake-induced vibration. More specifically, this paper examinesthe effect of the soil saturation leveltaking into account of soil-structureinteraction (SSI) on the structural response. For this purpose, a twodimensional (2D) finite element model was developed with Mohr-Coulomb failurecriterion under plane-strain conditions using geotechnical ﬁnite element codePLAXIS. To emphasize SSI problems in civil engineering applications, mechanicalbehavior and various saturation levelsof the local soil condition is examinedusing a numerical model. As can seen from the analysis results, thesaturation level of soils causes an increase on the lateral roof displacement ofthe saturated elasto-plastic soil. This situation was interpreted as theincrease in the saturation levels of the soils caused a decrease in therigidity. Furthermore, neglecting the effect of SSI leads to underestimatedresults of the structural behavior.